Penerapan Activity Based Costing dan Time Driven Activity Based Costing untuk Menghitung Unit Cost Kamar Rawat Inap pada Rumah Sakit X - Sukamto Sukamto; Hanif Ismail (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to examine the existing method of calculating inpatient room unit costs and to compare it with calculations based on Activity-Based Costing (ABC) and Time-Driven Activity-Based Costing (TDABC), as well as to analyze the implications of these approaches for inpatient room tariff policies.  The research adopts a case study method. Data analysis is conducted using a combination of qualitative and quantitative approaches, utilizing both primary and secondary data. Primary data are collected through in-depth interviews.  The findings indicate that the conventional unit cost calculation method currently in use is no longer aligned with the actual conditions of the hospital, as it produces cost distortions when compared to the ABC–TDABC approach. In contrast, the ABC–TDABC method more accurately reflects the real unit cost under the hospital’s operational conditions, resulting in more precise inpatient room cost calculations.  Furthermore, the results of the ABC–TDABC-based unit cost calculation are used to adjust the determination of inpatient room tariffs. The establishment of appropriate inpatient room tariffs is expected to enhance price competitiveness and improve service margin performance.